Treatment to target in psoriatic arthritis with apremilast: probability of achieving targets and comprehensive control of disease manifestations - Mease, PJ; Gladman, DD; Ogdie, A; Coates, LC; Behrens, F; Kavanaugh, A; Mcinnes, I; Queiro, R; Guerette, B; Brunori, M; Teng, L; Smolen, JS (Wiley, 2020)
Objective: To evaluate the probability of achieving Clinical Disease Activity for Psoriatic Arthritis (cDAPSA) treatment targets of remission (REM) or low disease activity (LDA) with apremilast based on disease activity categories and corresponding responses in arthritis and other domains of psoriatic arthritis (PsA) not included in cDAPSA. Methods: Pooled PALACE 1‐3 analyses were performed. Probability analyses assessing the likelihood of achieving cDAPSA treatment targets by Week 52 were performed using multiple imputation for discontinuations and missing values. Longitudinal analyses were performed in patients grouped by cDAPSA category at Week 52. Results: Among 494 patients in the probability analyses, 46.9% with moderate and 24.9% with high disease activity at baseline achieved treatment targets (REM or LDA) by Week 52. For patients with moderate disease activity at baseline, small improvements (cDAPSA reductions ≥30%) by Week 16 were associated with achieving targets; patients achieving REM or LDA by Week 16 had high probabilities of remaining at treatment targets at Week 52. Of 375 patients with cDAPSA components available at Week 52, achieving targets with apremilast was associated with continuous disease activity improvements and no or mild arthritis and other PsA manifestations. Conclusion: The probability of achieving treatment targets (REM or LDA) at Week 52 was greater for patients with moderate versus high disease activity at baseline. At a mean level, partial improvements by Week 16 were associated with achieving treatment targets. Patients receiving apremilast who achieved cDAPSA targets by Week 52 also had no or mild arthritis and other PsA manifestations.